Informaçao, crença e decisao: perspectiva de pesquisa de um vértice do comportamento gerencial - Nassif, Mônica Erichsen (2017)
This article is a preliminary review of the literature from a research perspective that aims to study the behavior of the decision maker, from a contemporary cognitive and behavioral point of view. Based on the results of completed research, there is a need to increase the studies about the emotional and affective aspects related to the behavior of decision makers, which have a profound impact on the search and use of information. In contemporary cognitive and behavioral studies, emotions, transposed into beliefs, are considered determinants of behavior, interactions, and decisions of the subject. In view of this, it is a research perspective to identify the relationship between the beliefs of decision makers and the search and use of information, from the point of view of information management and knowledge, from the theoretical foundations of situated and incorporated cognition and of cognitive therapy, presented in this article